An in-situ experimental and numerical evaluation on thermoelectric generators performance utilizing diesel engine exhaust heat - Sugiyanto, Sugiyanto; Aisyah, Nyayu; Prayitno, Yosephus Ardean Kurnianto; Bahiuddin, Irfan (Jurnal Polimesin, 2025)
Waste Heat Recovery (WHR) from heavy-duty diesel generators using Thermoelectric Generators (TEGs) offers a potential way to improve total system efficiency and reduce fuel consumption. This study combines experiments and numerical simulation to evaluate the performance of Hi-Z HZ 14 TEGs modules applied to a 6-cylinder, 60 kVA diesel generator. Experimentally, TEG modules were mounted equidistantly along the exhaust manifold, 40 cm from the engine, and tested at idle (750 rpm) with and without active air-side cooling. Hot- and cold-side temperatures, open-circuit Voltage (Voc), load power, and conversion efficiency were recorded. A matching TEG configuration was simulated under the same boundary conditions. As a result, active cooling increased the temperature differential and consistently improved power output and efficiency relative to natural convection. An efficiency of 2.1% was observed, in reasonable agreement with the simulation and consistent with typical TEGs performance under comparable operating conditions. Although this value confirms the feasibility of TEG integration in heavy-duty diesel exhaust systems, further improvements are possible through material selection, heat-sink optimization, and advanced cooling strategies.